Improvement of Conversion Efficiency of Silicon Solar Cells by Submicron‐Textured Rear Reflector Obtained by Metal‐Assisted Chemical Etching. Issue 7 (20th June 2017) - Irishika, Daichi; Onitsuka, Yuya; Imamura, Kentaro; Kobayashi, Hikaru
Abstract : A 19.8% conversion efficiency has been achieved by formation of a nanocrystalline Si layer on the front surface and a submicron‐textured reflector on the rear surface of monocrystalline Si solar cells. The nanocrystalline Si layer with a thickness of ∼200 nm formed by the surface structure chemical transfer (SSCT) method significantly decreases the front surface reflectance to less than 3%, while the submicron‐textured rear surface formed by the metal‐assisted chemical etching (MACE) method enhances light absorption inside Si. Both the reaction rates of the SSCT and MACE methods do not depend on crystal orientations, and therefore, these methods are applicable to polycrystalline Si solar cells. Reflectance spectra in the wavelength region longer than 950 nm of the nanocrystalline Si layer/Si structure show that the submicron‐textured reflector has excellent light trapping effect equivalent to the pyramidal textured reflector. Due to this light trapping effect, the short‐circuit photocurrent density of the nanocrystalline Si solar cells has been improved to 41.6 mA cm −2 . Abstract : Formation of a nanocrystalline Si layer on the front surface achieves ultralow reflectance and a submicron‐textured structure on the rear surface greatly increases the optical path length. By use of these structures in crystalline Si solar cells, a high photocurrent density of 41.6 mA cm −2 and a 19.8% conversion efficiency have been achieved in spite of the simple solar cell structure without anti‐reflection coating.